Application of the public–private partnership model to urban sewage treatment. (20th January 2017) - Yang, Tong; Long, Ruyin; Cui, Xiaotong; Zhu, Dandan; Chen, Hong
Abstract: Funding shortages can greatly affect the construction and implementation of urban sewage treatment projects. Applying the public–private partnership model to urban sewage treatment projects will increase the financing capacity and mitigate the risk of local debt. Based on analyses of current urban sewage treatment projects and the relationship between the public–private partnership model and these projects, we demonstrated that the public–private partnership model is applicable to city sewage treatment projects, thereby enhancing social capital, improving the management and operation of the projects, and facilitating various management methods for innovation and optimization. We studied the relationships between responsibility and authority, benefit sharing, and risk sharing using the public–private partnership model as well as the main issues that affect urban sewage treatment, and we then analyzed these issues from the perspectives of government, enterprises, intermediary agencies, and public groups. We conclude that the implementation of public–private partnership models affects urban sewage treatment projects by defining the relationship between the government and market. Based on our comprehensive analysis, we provide policy suggestions regarding the public–private partnership model for urban sewage treatment with respect to government, social capital, and intermediary organizations, thereby providing a guide to the implementation of the public–private partnership model. Highlights: Funding shortages are the main problem affecting urban sewage treatment projects. A win–win situation can be achieved by implementing PPP for urban sewage treatment. Government's role in PPP should be defined for the urban sewage treatment projects. Analyze social capital participation in PPP from enterprise to industry. Intermediaries link the government and social capital in PPP.